Quality improvement in neurocritical care: current state and looking to the future. Issue 2 (April 2020) - Moheet, Asma M.; Livesay, Sarah L.
Abstract : Purpose of review: Neurocritical care has matured as a field and there is now a growing body of literature on the subject of quality improvement in neurocritically ill patients. This review will highlight major recent contributions in this field and discuss future directions. Recent findings: Articles published in the past 18 months have evaluated neurocritical care unit staffing, structure, and disease-specific protocols including subarachnoid hemorrhage and severe traumatic brain injury management. An assessment of current quality improvement practices in neurocritical care was also conducted. A neurocritical care-specific metric bundle is being proposed. Summary: The quality improvement movement is gaining momentum in neurocritical care with evaluation of general medical and surgical critical care quality improvement approaches in this specific patient population. Future work should focus on improving systems of neurocritical care delivery through iterative evaluation of structure, staffing, minimizing unnecessary variation, and evaluation of neurocritical care-specific metrics.